Synergistic construction of high-performance lithium-sulfur batteries with sulfur-free cathodes and CMK-3 modified separators - Guohong Kang; Furan Wang; Tiancheng Wang; Zehao Shi; Shengrui Cui; Ning Wang; Ge Su; Zengqi Zhang; Wei Liu; Yongcheng Jin (Carbon Future)
Lithium-sulfur (Li-S) batteries are considered a leading candidate for advanced energy storage applications, primarily because of their exceptional energy density. However, their commercialization remains challenged by persistent obstacles, including slow reaction kinetics, volumetric electrode changes, and shuttle effects. Herein, a novel configuration of Li-S batteries is proposed. It is constructed by a S-free cathode, a polypropylene (PP) separator modified by CMK-3, and an electrolyte containing Li2S6. This simplifies the fabrication process of Li-S batteries, greatly improving active material utilization and mitigating the shuttle effect. The porous cathode effectively absorbs long-chain polysulfides and facilitates their redox. Similarly, the CMK-3 modified separator can also serve as a second reaction field, which suppresses polysulfide shuttle and enhances the utilization efficiency of active materials. The results indicate that under the synergistic effects of the S-free cathode and modified separator, the batteries exhibit excellent performance at low temperature or high rate. The fabricated batteries exhibit an initial capacity of 1082 mAh∙g−1 at 2 C, and retain 906 mAh∙g−1 after 200 cycles. Furthermore, these batteries demonstrate a discharge capacity reaching 1189 mAh∙g−1 at −15 °C and 0.1 C. This method introduces an innovative approach to simplify the preparation process of Li-S cathodes.